5PSQ-103 Parental unmet needs on paediatric drugs expressed in forums. Issue 1 (23rd March 2023) - Vilimelis, I; Pérez-Ricart, A; Bosch Peligero, M; Calvo, A; Codina-Jiménez, C; Valls Sánchez, E; Suñé Negre, JM; Quiñones Ribas, C; Giménez-Juárez, JC
Abstract : Background and Importance: Social Media (SM) could be a source of unmet needs of parents about drug use in paediatrics. Knowing subjective information (SI) can lead to improve pharmaceutical care. Aim and Objectives: Analyse content of posts from parent forums (PF). Material and Methods: Observational, ambispective study on PF related to primary care medicines in paediatrics. PF were selected if included child-health sections in Catalan, Spanish or English and permission was obtained. Data mining software was developed using ontologies from Spanish Agency of Medicines and Medical Devices and Medical Dictionary for Regulatory Activities. Posts were excluded if written by professionals, referred to non-pharmacological treatments, adults, pregnancy, hospital drugs, non-original entries or duplicates. SI was classified into positive, negative or doubts according tone and adjectives expressed. Results: 3572 posts from two PF were downloaded, 821 (26%) analysed. Excluded entries (94;11%): non-pharmacological treatments (42;5%), hospital drugs (12;1%), adults (12;1%), non-originalentries (9;1%), pregnancy (2;0, 02%) or duplicates (2;0, 02%).444 (72%) users mentioned SI in 591 posts (1, 3 SI/post). Notifier were mainly parents(177;40%) and caregivers (233;52%). SI posts contained neutral (223;38%), doubts (259;44%), negative (63;10%), positive (47;8%) SI. Posts referred to 453 children, infants (28 days-23 months) (156;26%) and children (3-11 years) (107;18%) and not classified (190;56%).Reported drugs: antibiotics (214;36%), respiratory (99;17%) and nervous system (78;13%) medications, other (200, 34%). Routes: oral (330;56%), parenteral (123;21%), other (138, 23%).Topics reported were: Conclusion and Relevance: Doubts, negative attitudes towards a future medicine and positive opinions about drugeffectiveness were the most SI expressed by PF users. Pharmacists can have a main roleproviding more information and knowledge to parents about drugs. References and/or Acknowledgements: Conflict of Interest: No conflict of interest